The Role Of Healthcare Workers In Preventing Surgical Site Infections: Evidence-Based Strategies And Interventions (The Review of Diabetic Studies, 2024)
Surgical site infections (SSIs) are a significant healthcare burden, accounting for 15.7% of healthcare-associated infections. Evidence-based guidelines recommend interventions such as rational antibiotic prophylaxis, appropriate preoperative hair removal, perioperative normothermia, and glycemic control to reduce SSI incidence. However, suboptimal adherence to these measures necessitates further research to evaluate the effectiveness of care bundles and reinforce their importance in clinical practice. Recent systematic reviews and meta-analyses have identified antimicrobial sutures as a promising intervention, demonstrating significant SSI reductions across various surgical specialties. This evidence supports their inclusion in standardized care bundles. Other interventions like 2% chlorhexidine in alcohol-based skin preparation, postoperative negative pressure wound therapy, and antiseptic wound dressings show potential but require further validation. Practices such as preoperative bathing/showering, antibiotic prophylaxis for clean non-prosthetic surgeries, and perioperative oxygen supplementation remain contentious. Evidence indicates that wound guards and diathermy skin incisions do not significantly impact SSI rates. Integrating these insights into clinical practice can improve adherence to evidence-based guidelines and reduce the prevalence and impact of SSIs. Future research should focus on standardizing protocols, conducting well-powered trials, and assessing interventions in specific surgical populations to provide clearer guidance for SSI prevention.